Host genetics and viral load in primary HIV-1 infection: clear evidence for gene by sex interactions. - Li, X; Price, M; He, D; Kamali, A; Karita, E; Lakhi, S; Sanders, E; Anzala, O; Amornkul, P; Allen, S; Hunter, E; Kaslow, R; et al. (2014)
Research in the past two decades has generated unequivocal evidence that host genetic variations substantially account for the heterogeneous outcomes following human immunodeficiency virus type 1 (HIV-1) infection. In particular, genes encoding human leukocyte antigens (HLA) have various alleles, haplotypes, or specific motifs that can dictate the set-point (a relatively steady state) of plasma viral load (VL), although rapid viral evolution driven by innate and acquired immune responses can obscure the long-term relationships between HLA genotypes and HIV-1-related outcomes. In our analyses of VL data from 521 recent HIV-1 seroconverters enrolled from eastern and southern Africa, HLA-A*03:01 was strongly and persistently associated with low VL in women (frequency = 11.3 %, P < 0.0001) but not in men (frequency = 7.7 %, P = 0.66). This novel sex by HLA interaction (P = 0.003, q = 0.090) did not extend to other frequent HLA class I alleles (n = 34), although HLA-C*18:01 also showed a weak association with low VL in women only (frequency = 9.3 %, P = 0.042, q > 0.50). In a reduced multivariable model, age, sex, geography (clinical sites), previously identified HLA factors (HLA-B*18, B*45, B*53, and B*57), and the interaction term for female sex and HLA-A*03:01 collectively explained 17.0 % of the overall variance in geometric mean VL over a 3-year follow-up period (P < 0.0001). Multiple sensitivity analyses of longitudinal and cross-sectional VL data yielded consistent results. These findings can serve as a proof of principle that the gap of "missing heritability" in quantitative genetics can be partially bridged by a systematic evaluation of sex-specific associations.